The Influence of Communication, Work Discipline, and Intrinsic Motivation on Employee Performance at Sentral Cawang Hotel East Jakarta - Wahadi Siamto; Whina Ratnawati; Rio Setiawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine partially and simultaneously the variables of Communication and Work Discipline on Employee Performance at the Sentral Cawang Hotel, East Jakarta. The research method used is a quantitative method using a questionnaire that is transformed with a Likert scale that is processed with SPS software and analyzed the data using a hypothesis test, namely the T test and F test and using the coefficient of determination test. The results of this study are Partially and simultaneously variable x has a significant effect on variable Y and the influence of the variables Communication, Work Discipline and Intrinsic Motivation on Employee Performance is 76.70% and the remaining 23.30% is influenced by other factors.